2009
DOI: 10.1016/s1472-6483(10)60015-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for preimplantation genetic screening in repeated pregnancy loss

Abstract: The objective of this study was to identify specific subgroups of recurrent pregnancy loss (RPL) patients of unknown aetiology in whom the selection of chromosomally normal embryos for transfer improves reproductive outcome in preimplantation genetic screening (PGS). A total of 428 PGS cycles were included and chromosomes 13, 15, 16, 18, 21, 22, X and Y were evaluated. In RPL patients < or =37 years, a lower incidence of chromosomal abnormalities (P = 0.0004) and miscarriages (P = 0.0283) was observed, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 60 publications
1
27
0
2
Order By: Relevance
“…PGS utilizes either FISH or array-based analysis to detect chromosomal abnormalities or genetic defects in embryos undergoing IVF/ICSI [5]. PGS can also be used to identify embryos without aneuploidy or an unbalanced translocation for implantation in the female [22].…”
Section: Genetic Counselingmentioning
confidence: 99%
“…PGS utilizes either FISH or array-based analysis to detect chromosomal abnormalities or genetic defects in embryos undergoing IVF/ICSI [5]. PGS can also be used to identify embryos without aneuploidy or an unbalanced translocation for implantation in the female [22].…”
Section: Genetic Counselingmentioning
confidence: 99%
“…For chromosome determination, eggs were fixed using our technique (37,38) with some modifications. In short, the ZP and two PB were removed to avoid chromosome signal interferences.…”
Section: Chromosome Analysismentioning
confidence: 99%
“…This version of PGS can be called first-generation PGS. Initial studies with first-generation PGS suggested that implantation rates increased and loss rates decreased (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, other studies, including several randomized controlled trials (RCTs), showed no benefit (29)(30)(31)(32)(33)(34)(35)(36) or, worse, a negative impact on implantation, pregnancy, or loss rates (37,38).…”
mentioning
confidence: 99%